The Prayer of Freedom and Contingency of Human in Etty Hillesum’s Diaries - Mizdrak, Inga (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The experience of freedom, treated in various ways by philosophy, psychology, sociology, theology and politics, is shown as an infinite category. Its complexity and problematic matter is concerned not only with unlimited intellectual interpretations but also with the ways it is treated. From various ways of revealing the phenomenon of freedom, in the context of human contingency, the way of dialogue is prominent, which reveals one of the most important traits which freedom is. The original reflection, included in Etty Hillesum’s diaries (An Interrupted Life) reveals the basic feature of freedom: its relatedness, the deepest expression of which is achieved through one’s relationship with God. Through this feature, the trait of the human him- or herself is shown as he or she is able to direct him- or herself towards love or hate, life or death, beauty or ugliness, good or evil. Etty Hillesum herself is for life as it is, and she becomes the real ambassador of life through vertical relations with God, even in the face of extreme danger, injustice and the cruelty of war. In this context, life is not treated as the dominant and oppressive contingency but as a time of kairos, which means something that can be creatively and positively used to make human values and become a witness of life fulfilled by the element of eternity. In this light, the main goal of this study is to present a few basic threads of the description of humanity, as extracted from Hillesum’s self-reflective writing. By delving into the description of Hillesum’s inner world, an attempt is made to characterise those elements in the subjectivity of the human, which emphasises the specific individuum as being immersed in relations with himself, others and God.